Theory of speckle suppression in a laser projector based on a long multimode fiber. (December 2021) - Lapchuk, A.S.; Xu, Qiyong; Le, Zichun; Zhou, Jun; Liu, Zongshen; Cai, Di; Prygun, O.V.; Kryuchyn, A.A.
Highlights: We have developed first time a rigorous theoretical model for describing a practical laser projection system with a finite aperture of the objective lens and finite length of multimode fiber. The theoretical analysis and simulations indicate that the speckle suppression coefficient can be approximated as a linear function of the square root of the ratio of the numerical aperture of the objective lens and the eye. The theoretical and experimental results indicate that the decorrelation uses only the radial direction of the objective lens aperture for speckle suppression and does not consider the azimuthal direction, which can be the focus of future studies. The speckle contrast data obtained in our experiments are consistent with the theoretical results. Abstract: We analyzed the speckle suppression efficiency of a multimode fiber in a practical laser projector, and developed a theoretical model. Theoretical analysis and simulations indicate that the speckle suppression coefficient can be approximated as a linear function of the square root of the ratio of the numerical aperture of the objective lens and the eye. To suppress the speckle below human eye sensitivity, the objective lens should have a large numerical aperture. The decorrelation uses only the radial direction of the objective lens aperture for speckle suppression and does not consider the azimuthal direction, which can be the focus of future studies. The speckle contrast data obtained in the experiments are consistent with the theoretical results.